Fostering Resilience among Orphaned Adolescents through Institutional Care in India. Issue 4 (2nd October 2019) - Mishra, Rachna; Sondhi, Vanita
ABSTRACT: This study tries to identify the role of institutional care in promoting resilience among a group of orphaned adolescents ( n = 20). It was hypothesized that the orphanage care will have a significant role in contributing toward positive outcomes among participants. Twelve females and eight males in the age-range of 12–19 years and residing in five orphanages participated in focus groups. Before group discussions, participants were asked to draw self-portrayals to explore any changes that they perceive in themselves before versus after being placed in the institution. It was observed that by reducing participants' anxiety about their future, providing opportunities to focus on higher-order goals and furnishing other growth-fostering resources, the institutional care promotes a determination among the adolescents to achieve a positive change in their lives. This study makes a strong point in favor of considering the institutional care model as a viable option when others are unfeasible.